Fault Analysis of Power Distribution Network Using FTA and FMEA: A Study at PT PLN - WASKITA, FARID (KH. A. Wahab Hasbullah University, 2024)
PT. PLN is a supplier of electrical energy in Indonesia which plays an important role in providing sufficient electricity for daily activities, industry and other sectors. UPDK Kapuas is a power plant in Pontianak City. Based on SAIDI and SAIFI data, the duration and frequency of blackouts in 2021 is 14.85 hours per customer per year and 14.5 times per customer per year, while in 2022 it will be 16.85 hours per customer per year and 17.16 times per customer. This has increased every year. Then the average loss value in 2022 will be 11% and the average Energy Not Supplied (ENS) value will be 26,265 kWh/month. Based on the Fault Tree Analysis method, there are 25 causes of network disruption from internal and external. Of the 25 causes of network disruption, it was reduced based on the minimum Cut Set results to 5, namely, damage caused by natural disturbances, animals, humans, installation errors, and electrical component disturbances. The highest RPN value result was caused by electrical cables amounting to 11638 which needed to be a priority repair by UPDK Kapuas. Recommendations for improvement include carrying out routine maintenance and maintenance of the network to prevent damage and adding Thermovision tools to identify and detect network damage more quickly and precisely.